2012
DOI: 10.1128/aac.00700-12
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Omeprazole To Augment Subtherapeutic Voriconazole Concentrations for Treatment of Aspergillus Infections

Abstract: Voriconazole is the preferred antifungal agent for Aspergillus infections. Therapeutic drug monitoring is recommended to achieve target concentrations and prevent toxicity. However, variable pharmacokinetics, cytochrome P450 polymorphisms, and extensive drug-drug interactions can contribute to subtherapeutic concentrations. We report a voriconazole "boosting" effect of omeprazole to achieve target concentrations for the treatment of Aspergillus in a patient who had persistently subtherapeutic trough concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 10 publications
1
22
2
1
Order By: Relevance
“…PPI treatment, in fact, remained a significant predictor of low VPCs in multivariate analysis. These findings are in contrast to previous findings reporting increased VPCs in cases of concomitant PPI use (8,22,23). Other studies, however, found no effect of PPI treatment on the pharmacokinetics of voriconazole (24).…”
Section: Discussioncontrasting
confidence: 56%
“…PPI treatment, in fact, remained a significant predictor of low VPCs in multivariate analysis. These findings are in contrast to previous findings reporting increased VPCs in cases of concomitant PPI use (8,22,23). Other studies, however, found no effect of PPI treatment on the pharmacokinetics of voriconazole (24).…”
Section: Discussioncontrasting
confidence: 56%
“…Several clinical studies evaluating voriconazole therapeutic drug monitoring and factors affecting plasma concentrations have reported an association between concomitant PPI use and elevated voriconazole concentrations (5,12,23). Furthermore, case reports of the occurrence of increased plasma voriconazole concentrations after coadministration of voriconazole with a PPI have also been reported; two of the reports were distinct, in that the studies involved the deliberate use of a PPI to boost voriconazole concentrations into the therapeutic range (19,20,37). For patients in whom higher plasma voriconazole levels are required to improve tissue penetration or to overcome rapid metabolism, PPI-mediated inhibition could be a reasonable solution for achieving target voriconazole concentrations, provided that TDM is available to guide therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Both voriconazole and PPIs are also vulnerable to the significant pharmacokinetic variability associated with CYP2C19 polymorphisms. Unsurprisingly, increased plasma voriconazole concentrations during coadministration with a PPI have been reported (5,12,19,20). Despite the widespread use of PPIs and the potential for CYP450-mediated interactions with voriconazole (12,17), the net effect of PPIs on voriconazole pharmacokinetics has not been delineated.…”
mentioning
confidence: 99%
“…In many patients, this will lead to a dose reduction from that given initially, but some patients will require even higher doses to achieve those concentrations, which suggests that some patients have more rapid metabolism. 13 Surgery plays an important role in patients who have epidural abscess or phlegmon.…”
Section: Drugs and Dosesmentioning
confidence: 99%